The role of streets in improving urban livability Case study: Aleppo, Al-Hamdaniya (Neighborhood three) (Damascus University Journal for engineering sciences, 2024)
Many cities are facing threats to the future of livability in their communities, as the paid economic growth and urbanization have led to a massive change in the built environment and the society. Also have led to create residential neighborhoods which planners prioritized cars' movement, this transformed most of the streets to become just roads for cars instead of being also a suitable place for social life, and this has resulted in a wide range of negative impacts on both health, environment, and quality of life, so the research explored the problem of the absence of the role of the streets improving the concept of the urban livability, so it aimed to explain the concept deeply, and then studied the relationship between urban livability and streets. The research used the descriptive-analytical approach during the literature review stage, and the descriptive-analytical approach in reviewing the current status of the case study, also used the quantitative approach and treatments statistics to determine whether there is a correlation between streets with their dimensions and urban livability, and the method of collecting the primary data was the a questionnaire, which was designed to achieve the goal of the study and in which the five-point Likert scale was used, and distributed to 104 individuals who were chosen in a simple random way to ensure the representation of the various members of the study community, and 94 forms were retrieved for analysis, and after doing the statistical treatments for the data, results according to the views of the study sample showed that there is a correlation and a positive impact between urban livability and the achievement of urban design of the streets for the environmental and social dimension, as the increased interest in them will be reflected on the increase in urban livability, in the other hand there was a positive correlation without an effect between urban livability and the achievement of urban design for the streets for the economic, health and urban-functional dimensions, and there was no correlation or impact between urban livability and the achievement of urban design of the streets for the security dimension. The research recommends the developers and planners to prioritize the environmental and social dimensions during the Urban design stage of streets and developing current streets to be an active    and important factor in upgrading the urban livability.
Keywords: Urban Design; Urban Livability; livable Neighbourhood; Streets; Indicators; Principles; Upgrading